Analisis Dampak Media Sosial Facebook pada Komunikasi Interpersonal dalam Keluarga di Desa Pulau Binjai Kabupaten Kuantan Mudik Riau - Muhammad Ilham Prastono (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2021)
This research is motivated by advances in communication technology that provide many good benefits in life. In addition to the good benefits, technological advances also have a negative effect on the social environment. The impact of social media makes a person to be indifferent to the people around him, indifferent, inattentive which can change interpersonal communication in the family scope. Changes in interpersonal communication are a life phenomenon experienced by everyone anytime and anywhere, one of which is in the family environment. In this study, the researcher used a qualitative approach with the type of field research. Collecting data through observation, documentation and interviews, and then analyzed descriptively qualitatively. The findings showed that the family's interpersonal communication situation did not go well due to a lack of self-disclosure to their family and lack of empathy, this also resulted in a change in their interpersonal communication behavior. From this study it can be concluded that changes in family interpersonal communication behavior due to the use of online social media have occurred in families in Pulau Binjai Village, Kuantan Mudik District, Kuantan Singingi Regency.